What Keeps Elderly Indonesians Working? - Elfisa Putri; Dyah Wulan Sari (Muhammadiyah University Press, 2021)
The era of the baby boom and the improvement in the quality of life brought the Indonesian population to an aging phase. The increasing elderly population in Indonesia is not in line with the labor force participation rate of the elderly which tends to stagnant and decline based on BPS data from 2003 to2019. This study aims to examine the determinants of the participation of the elderly to work, not only from the supply side but also from the demand side of the labor market that has never been studied in the Indonesian elderly. We use the 2018 Susenas and the 2018 Podes by Badan Pusat Statistik (BPS). We used logistic regression to analyze the variables that drive the elderly to work. From the results of the study, it is known that with a confidence level of 1 percent, poverty status, the distance to urban centers (access to work) and village industrial structure (with the agricultural sector) plays a role in increasing the opportunities for the elderly to work. While the living arrangement, age, education, and ownership of pensions contribute otherwise.There is a corrigendum for this article: https://journals.ums.ac.id/index.php/JEP/article/view/16187